2008
DOI: 10.3177/jnsv.54.353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Folate on Notch Signaling and Cell Proliferation in Neural Stem Cells of Neonatal Rats In Vitro

Abstract: SummaryThe aim of the present study was to determine if folate alters Notch signaling and cell proliferation in neural stem cells (NSCs). NSCs were isolated from neonatal rats and grown in serum-free suspension culture. The cells were identified as NSCs by their expression of immunoreactive nestin. Individual cultures were assigned to one of three treatment groups: vehicle control, low-dose folate group (Folate-L, liquid media contained 4 mg/L folate), or high-dose folate group (Folate-H, liquid media containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…The latter data are consistent with the previous demonstrations that folic acid is able to stimulate Notch signaling, including Hes1 transcription, and promotes cell proliferation in neural stem cells [7577]. Taken together, the positive impact observed after folic acid supplementation and following siRNA strategy, along with the associated normalization of let-7a and miR-34a, strengthen the potential role of these microRNAs and their related signaling pathways in the developmental defects consecutive to gestational methyl donor deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…The latter data are consistent with the previous demonstrations that folic acid is able to stimulate Notch signaling, including Hes1 transcription, and promotes cell proliferation in neural stem cells [7577]. Taken together, the positive impact observed after folic acid supplementation and following siRNA strategy, along with the associated normalization of let-7a and miR-34a, strengthen the potential role of these microRNAs and their related signaling pathways in the developmental defects consecutive to gestational methyl donor deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have demonstrated a link between folate deficiency during early pregnancy and developmental abnormalities, such as neural tube defects [10], abnormal embryonic development [11,12], and tumor formation [13]. For these reasons, dietary folate supplementation is routinely recommended during early pregnancy in human [14].…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Zhang et al on neonatal rats showed that folate altered Notch signaling, which regulates the control of proliferation and differentiation in neural stem cells. Compared to the control, folate increased the rate of cell proliferation by increasing expression of Notch1 and Hes1 , while decreasing expression of Mash1 (43). All three genes are components of the Notch signaling pathway.…”
Section: The Aldh1 Family: Enzymes Implicated In Folate and Ethanol Mmentioning
confidence: 94%